Demografia polityczna i możliwości dla polityki pronatalistycznej w Polsce - Łakomy, Mateusz (Studia Demograficzne, 2016)
Political demography links demographic findings with public policies aimed at achieving state goals. Current challenge of population aging causes threat to internal financial stability and well-being of the elderly. Aging also questions countries’ international position due to possibly reduced financial capability to maintain geopolitical power, and in extreme situation of lowest low fertility also due to continuous, unstoppable decline in the population size. In case of Poland, aging alone would result in almost doubling expenditure on pensions and healthcare. To respond to social and geopolitical challenges, the government should primarily focus on policies aimed at stimulating births. To foster pronatalist policies, factors affecting fertility may be grouped into five categories: economic, cultural, psychological, infrastructural and unplanned. All these factors influence childbearing behaviour simultaneously. Some of them constitute barriers to fertility (which need to be eliminated) and the others facilitate fertility (and they need to be strengthened). The barriers include financial constraints, individualistic values, financial insecurity, union instability, insufficient support network and lack of family-friendly employment. Identified facilitators in turn include pension system linking benefits with number of children (family pension system) and family-oriented aspirations and values with religion as a vital ingredient. Father commitment to family life impacts both as facilitator and by eliminating barriers.